Sports and Meaningful of Life: How is The Process to Achieve Meaningful of Life Athletes With Physical Disabilities? - Yahya Eko Nopiyanto; Rita Shintia; Dian Pujianto (UNIB Press, 2022)
The process of achieving the meaning of life is not easy for every individual because it is not only related to pleasant life experiences but also tragic or traumatic life experiences. Failure to find and fulfill the meaning of life usually leads to an appreciation of life without meaning, emptiness, feeling that you have no purpose in life, and feeling that your life is meaningless. One of the individuals who have difficulty in the process of finding the meaning of life is an athlete with a physical disability at the National Paralympic Committee (NPC) Bengkulu Province. Therefore, an in-depth study is needed regarding the process of achieving meaningfulness in the lives of athletes with physical disabilities at the Bengkulu Province NPC. This research was conducted with qualitative research methods. Respondents in this study consisted of 5 quadriplegic athletes, consisting of 5male athletes. Collecting research data using interviews. The results of the study stated that each respondent went through 5 stages to achieve the meaning of life, namely the stages of suffering, self-acceptance, the discovery of the meaning of life, realization of meaning, and meaningful life. In the first stage, each respondent experienced suffering because they were looked down upon or bullied by the people around them. In the second stage, each respondent begins to accept himself with resignation, patience, and sincerity in living life. In the third stage, each respondent successfully went through the process of finding meaning with the support of parents and family. In the fourth stage, each respondent is committed to the life goals that have been set. In the fifth stage, each respondent lives a meaningful life by pursuing a profession as an athlete. So it can be concluded that the process of achieving the meaning of life for athletes with disabilities is through sports.